2019
DOI: 10.1039/c9ra06193b
|View full text |Cite
|
Sign up to set email alerts
|

A vanadate-based white light emitting luminescent material for temperature sensing

Abstract: White-light emitting CMV:Eu3+ sheets show a linear color variation depending on the ambient temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The temperature-dependent PL characteristics of the samples were obtained by referring to the strategy in ref. 26 which was evaluated by heating the samples sealed in a metallic box and kept them at a particular temperature, and then rapidly transferring the sample at a specific temperature from the heater to the fluorescence spectrophotometer for measurement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature-dependent PL characteristics of the samples were obtained by referring to the strategy in ref. 26 which was evaluated by heating the samples sealed in a metallic box and kept them at a particular temperature, and then rapidly transferring the sample at a specific temperature from the heater to the fluorescence spectrophotometer for measurement.…”
Section: Methodsmentioning
confidence: 99%
“…The temperature-dependent PL characteristics of the samples were obtained by referring to the strategy in ref. 26 which was evaluated by heating the samples sealed in a metallic box and kept them at a particular temperature, and then rapidly transferring the sample at a specic temperature from the heater to the uorescence spectrophotometer for measurement. Davolos' research shows that efficient ion substitution can be achieved when the ionic radii difference percentage (D r ) between dopant ions and replaced ions is within 30%.…”
Section: Fabrication Of Led Devices and Temperature-dependent Pl Meas...mentioning
confidence: 99%
“…Zhang et al reported Ca 5 Mg 4 V 6 O 24 :Eu 3+ powders for thermal sensing within 298−473 K range with thermal sensitivity of about 0.5% K −1 . 26 CaNb 2 O 6 :Eu 3+ and CaNb 2 O 6 :Eu 3+ ,Bi 3+ phosphors showed high thermal sensitivity of 1.8 and 3.8% K −1 , respectively. 27 Noteworthy, the reported thermometers have a quite complex host composition, which makes synthesis more difficult.…”
Section: ■ Introductionmentioning
confidence: 97%
“…This approach was successfully realized by several scientific groups. Zhang et al reported Ca 5 Mg 4 V 6 O 24 :Eu 3+ powders for thermal sensing within 298–473 K range with thermal sensitivity of about 0.5% K –1 . CaNb 2 O 6 :Eu 3+ and CaNb 2 O 6 :Eu 3+ ,Bi 3+ phosphors showed high thermal sensitivity of 1.8 and 3.8% K –1 , respectively .…”
Section: Introductionmentioning
confidence: 99%
“…White light emission has become a very important effect due to its application in displays, light emitting devices [1] and sensors [2][3][4]. More specifically, a host of different materials have been used to accomplish this effect, including yellow phosphor materials in combination with Si or III-V semiconducting diodes [1], organics [5], perovskites [6], quantum dots [7], metal-organic frameworks [8,9] and others.…”
Section: Introductionmentioning
confidence: 99%